Combined exergy analysis, energy integration and optimization of syngas and ammonia production plants: A cogeneration and syngas purification perspective. (20th January 2020) - Flórez-Orrego, Daniel; Sharma, Shivom; de Oliveira Junior, Silvio; Maréchal, François
Abstract: Modern ammonia production plants are equipped with efficient energy integration networks able to recover an important fraction of the waste heat exergy available throughout the chemical system. However, in order to drive the endothermic reforming reactions at high temperature, as well as the syngas purification and compression processes, additional energy must be supplied by costly non-renewable resources. Moreover, the choice of the carbon capture unit, based on either physical or chemical absorption systems, drastically affects the way in which the waste heat recovery must be performed, and whether one or more energy technologies should or not be integrated (e.g. heat pump). Meanwhile, the selection among various energy resources, e.g. the import of electricity over the autonomous combined heat and power production (CHP), strongly depends on the ratio between the prices of electricity and fuels consumed, as well as on the extent of the energy integration. Accordingly, a simple trial and error approach falls short in efficiently determining the most suitable operating conditions that enable the production plant to run under the minimum operating cost. Thus, by using a systematic methodology, the most suitable utility systems (cooling, refrigeration, and cogeneration) that satisfy the minimum energy requirement (MER) with the lowest energy consumption and operating cost, are selected. Consequently, the conventional plant efficiency is increased about 10% by using a mixed operating mode or autonomous operating mode with combined cycle. Furthermore, reduced cooling (23%) and heating (51%) requirements are expected when physical solvents are used. The lowest exergy consumption corresponds to mixed operating mode by using a physical absorption unit (27.76 GJ/tNH3 ). Finally, it is found that exergy efficiency drops 24% when the irreversibility in the upstream steps of feedstock obtainment are considered. Highlights: Conventional plant efficiency is increased 10% by operating in MIXED mode or AUTO mode with combined cycle. Reduced cooling (23%) and heating (51%) requirements are expected when physical solvent (DEPG) is used. Efficiency drop achieves up to 23.8 points when irreversibility in the upstream feedstock obtainment is considered. Lowest exergy consumption (27.76 GJ/tNH3 ) corresponds to MIXED operating mode by using a physical absorption unit. Improved energy integration profiles for chemical reactors allow identifying advanced energy saving alternatives.